The apparent focal depth, emergence angle, and take-off angle of seismic wave measured by YRY-4-type borehole strainmeter as one kind of strain seismograph - Tang, Lei; Qiu, Zehua; Fan, Junyi; Yin, Zhigang (Frontiers in Earth Science, 2023)
In theory, the observation objects and principles of strain seismograph and traditional pendulum seismograph are different, and the characteristics of observed signals should also be different. The observation results of pendulum seismograph with particle velocity as the observation object show that the propagation of seismic waves in inhomogeneous media will undergo refraction, reflection and attenuation. Then, what signal characteristics can be detected by strain seismograph in the same seismic wave propagation process is of great significance for understanding and explaining the observation results of strain seismograph. Using YRY-4 type four-gauge borehole strainmeter as one kind of strain seismograph to detect the strain tensor change of the plane seismic wave emitted from the surface, a five-site strain seismograph observation network was built in Shanxi Province, with continuous observation for 2 years at a sampling rate of 100 times per second. In this paper, two local events occurred in the area covered by the strain seismograph observation network are taken as examples. We systematically studied the characteristics of seismic wave signals recorded by strain seismographs at five sites, inverted the focal depth of the two local earthquakes and the relationship between the wave velocity and the wave velocity gradient of the focal depth, and calculated the apparent focal depth, the emergence angle and the take-off angle of seismic waves. These results show stable uniqueness and obvious regularity, especially the inverted focal depths are basically consistent with the interpretation results of traditional pendulum seismograph. The research in this paper shows that the strain seismograph can be used as an effective supplement to the pendulum seismograph. In the future, we will continue to study the rupture process and focal mechanism of moderate-strong earthquakes and teleseismic earthquakes by combining two kinds of observations.